Gebhard Kirchgässner, 60 years on - Feld, Lars P.; Savioz, Marcel; Schnellenbach, Jan (Public choice, 2010)
This introductory essay summarizes the contents of the papers presented at a conference in honor of Gebhard Kirchgässner entitled “(Macro-)Economic Policy and Public Choice” which are published in this special issue. In addition to this brief overview on the contributions, this essay relates them to the scientific works of Gebhard Kirchgässner after locating the latter within the realm of Public Choice analysis.